Building human capital and dynamic managerial capability to elevate organizational agility and performance: a strategic for SME resilience - Kusumawijaya, Ida Ketut; Astuti, Partiwi Dwi; Wartana, I Made Hedy; Adi, I Ketut Yudana (Business, Management and Economics Engineering, 2026)
Purpose – This study explores the strategic role of human capital, dynamic managerial capability, and organizational agility in driving organizational performance within SMEs in Bali, Indonesia. Research methodology – Investigates the direct and indirect effects of human capital and dynamic managerial capability on organizational performance, mediated by organizational agility. A quantitative survey was conducted with 396 SMEs, using PLS-SEM for data analysis. Findings – Human capital enhances organizational agility but does not directly impact performance, while dynamic managerial capability positively influences both agility and performance. Organizational agility is found to significantly improve performance and partially mediates the relationship between human capital, dynamic managerial capability, and organizational performance. This research contributes to the critical role of organizational agility in transforming internal competencies into tangible performance outcomes, especially under volatile market conditions. Research limitations – Research is limited by its geographic scope, cross-sectional design, and reliance on self-reported data. Future studies could explore the dynamic interplay of these factors across different regions and over time. Practical implications – SME managers should prioritize developing agile capabilities and enhancing dynamic managerial competencies to effectively convert human capital into improved organizational performance under volatile conditions. Originality/Value – Organizational agility as a crucial mechanism that translates internal competencies into tangible performance outcomes, especially under conditions of environmental turbulence.